Aqueous phase methylene blue (MB) dye removal by mixture of eucalyptus bark (EB) biomass and kaolin clay (KC) adsorbents: Kinetics, thermodynamics and isotherm modelling - Tan, T.; Sen, Tushar (Taylor and Francis, 2019)
In this study, the mixture of eucalyptus bark (EB) (Sheathiana) biomass and kaolin clay (KC) adsorbents are used in the removal of aqueous-phase methylene blue (MB) dye. The optimum mass ratio of 1 KC to 3 EB biomass was identified. The removal efficiency was studied under various physicochemical process parameters. Kinetic measurements showed that the process was multistep, rapid, and diffusion controlled and equilibrium reached within 100 min. The adsorption was best described by both the Freundlich and Langmuir isotherm models. Thermodynamic parameters suggested that the process was an endothermic, spontaneous, and irreversible in nature.